La historieta - Varas Cruz, Vanesa Victoria (2020)
The present Work of Professional sufficiency entitled: "The comic", aims to support the application of a learning session to second year high school students - EBR in the approach of managing their own learning, where students understand the background and the form of the comics whose theme is the common good in our society. The comprehension of texts is a competence that is necessary for the integral development of the human being and, in the confinement in which we find ourselves, education has to update itself and propose new tools to achieve this objective. Faced with this, the need arises to make students aware of the different tools that make them like reading a text through a virtual environment and it is precisely the comic that allows us to introduce young people to the world of reading. This is presented in a striking way, full of colors, symbols and onomatopoeias, where the reader can read without falling asleep in the attempt. This work proposes to develop mainly the capacities based on thought, that is, in the strengthening of the student's critical thinking. It is also contextualized and implemented to be applied in a virtual environment where all young people have access to the Internet and manage programs such as Blog, Classroom, Zoom, Quizizz and Google Forms.